2015
DOI: 10.1590/1677-3225v14n2a11
|View full text |Cite
|
Sign up to set email alerts
|

Dental bleaching agents with calcium and their effects on enamel microhardness and morphology

Abstract: Aim: To evaluate enamel microhardness and morphology after bleaching with hydrogen peroxide containing calcium in different concentrations. Methods: One hundred specimens of human teeth were ground and polished and had the initial microhardness evaluated. The specimens were randomly assigned into five groups (n=20): Group 1 -Control group (no treatment); Group 2 -Home Peroxide 6% (without calcium); Group 3 -Home Peroxide 7.5% (without calcium); Group 4 -White Class 6% (with calcium); Group 5 -White Class 7.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…Although no statistical significant results are seen in the present study (p > 0.005), some alterations do occur in the microstructure of enamel after bleaching agents. Pizani et al, 19 following their study on bleaching agents with and without calcium on enamel microstructure, showed that in association with higher concentration of HP, calcium may decrease the MH and structural changes on enamel. Calcium was introduced in the bleaching system to decrease and minimize the enamel structure alterations and loss of minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Although no statistical significant results are seen in the present study (p > 0.005), some alterations do occur in the microstructure of enamel after bleaching agents. Pizani et al, 19 following their study on bleaching agents with and without calcium on enamel microstructure, showed that in association with higher concentration of HP, calcium may decrease the MH and structural changes on enamel. Calcium was introduced in the bleaching system to decrease and minimize the enamel structure alterations and loss of minerals.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been shown that bleaching with 35-38% hydrogen peroxides may change enamel morphology and alter mineral content (3,4,(8)(9)(10) . Thus, efforts have been made to achieve a protocol capable of remineralizing bleached enamel, recovering microhardness loss and surface alterations (11)(12)(13)(14)(15) . This study was designed to assess and compare the effect of two remineralizing protocol using innovative biomimetic materials (Nano-BG and Nano-HA) on the structural integrity of bleached enamel surface, manifested by microharness and morphological changes in enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors contribute to the difficulty of repairing dental enamel tissue. (8,10) In order to minimize such demineralization after contact with bleaching agents, some ingredients such as fluoride (11)(12)(13) , calcium (14) or amorphous calcium phosphate (11) are added into the bleaching gel by manufacturers. Some biomimetic materials such as nano hydroxyapatite and nano structured bioactive glass have been advocated as new techniques for enamel reconstruction that have been a challenging topic of research in material sciences and dentistry .…”
Section: Introductionmentioning
confidence: 99%
“…The thickness and density affect the surface of the tooth crown. The composition of ORIGINAL RESEARCH 1,3,4 Department of Oral Biology, Faculty of Dentistry, University of Hasanuddin, Makassar, Indonesia elements of tooth enamel is composed of cells, organic matrix, and inorganic matrix; these cells control the initial production of tissue minerals. 1 Tooth enamel consist of consist of 96% inorganic material, 4% water, organic matter, and fibrous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The salts comprise of materials such as keratin (pseudokeratin), collagen, peptone, glycoproteins, polysaccharides, fats, and acids amino. 2,3 Enamel consists of the outer and inner enamel, which are enamel surface and subsurface enamel. Surface enamel contains more fluorine and a little carbonate so that the surface enamel is harder, less porous, insoluble, and more radiopaque.…”
Section: Introductionmentioning
confidence: 99%